Contained Left Ventricular Free Wall Rupture following Myocardial Infarction - Arthur Shiyovich; Lior Nesher (Case Reports in Critical Care, 2012)
Rupture of the free wall of the left ventricle occurs in approximately 4% of patients with infarcts and accounts for approximately 20% of the total mortality of patients with myocardial infractions. Relatively few cases are diagnosed before death. Several distinct clinical forms of ventricular free wall rupture have been identified. Sudden rupture with massive hemorrhage into the pericardium is the most common form; in a third of the cases, the course is subacute with slow and sometimes repetitive hemorrhage into the pericardial cavity. Left ventricular pseudoaneurysms generally occur as a consequence of left ventricular free wall rupture covered by a portion of pericardium, in contrast to a true aneurysm, which is formed of myocardial tissue. Here, we report a case of contained left ventricular free wall rupture following myocardial infarction.